Analysis of the completeness and consistency of records of violence against indigenous women in the health macro-region of Dourados, Mato Grosso do Sul state, Brazil, 2009-2020 - Glênio Alves de Freitas; Gláucia Elisete Barbosa Marcon; James Robert Welch; Cosme Marcelo Furtado Passos da Silva (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To analyze the temporal trend of completeness and consistency of data on notifications of violence against indigenous women in the health macro-region of Dourados, state of Mato Grosso do Sul, Brazil, between 2009 and 2020. Methods: An ecological time series study was conducted using data from the Notifiable Health Conditions Information System; Prais-Winsten regression was used to analyze the trend of data completeness and consistency, as well as the proportion of completed and coherent fields. Results: A total of 2,630 cases were reported; completeness was found to be very poor in the variable "occupation" (48.9%) and poor in the variables "schooling" (68.3%) and "time of occurrence" (67.9%); in the analysis of temporal trends, only the variable "occupation" showed a decreasing trend (p = 0.045). Conclusion: The data analyzed demonstrated the need for improvement in the completeness of the variables "schooling", "occupation" and "time of occurrence" of the violent act.